CognitionMaster: an object-based image analysis framework - Wienert, Stephan; Heim, Daniel; Kotani, Manato; Lindequist, Björn; Stenzinger, Albrecht; Ishii, Masaru; Hufnagl, Peter; Beil, Michael; Dietel, Manfred; Denkert, Carsten; Klauschen, Frederick (Diagnostic pathology, 2013)
Automated image analysis methods are becoming more and more important to extract and quantify image features in microscopy-based biomedical studies and several commercial or open-source tools are available. However, most of the approaches rely on pixel-wise operations, a concept that has limitations when high-level object features and relationships between objects are studied and if user-interactivity on the object-level is desired.
Gesehen am 08.11.2021